2010
DOI: 10.1371/journal.pone.0008669
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Urban Violent Injury: A Spatio-Temporal Analysis

Abstract: ObjectivesInjury related to violent acts is a problem in every society. Although some authors have examined the geography of violent crime, few have focused on the spatio-temporal patterns of violent injury and none have used an ambulance dataset to explore the spatial characteristics of injury. The purpose of this study was to describe the combined spatial and temporal characteristics of violent injury in a large urban centre.Methodology/Principal FindingsUsing a geomatics framework and geographic information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 19 publications
5
67
2
Order By: Relevance
“…1 The most common methods were either using a telephone triagederived dispatch determinant (most commonly the Medical Priority Dispatch System (MPDS)) [2][3][4][5] or 'a system devised by the authors'. [6][7][8][9][10][11] Categorisation using MPDS occurs at the point-of-call receipt, before ambulance arrival.…”
Section: Introductionmentioning
confidence: 99%
“…1 The most common methods were either using a telephone triagederived dispatch determinant (most commonly the Medical Priority Dispatch System (MPDS)) [2][3][4][5] or 'a system devised by the authors'. [6][7][8][9][10][11] Categorisation using MPDS occurs at the point-of-call receipt, before ambulance arrival.…”
Section: Introductionmentioning
confidence: 99%
“…One such Philadelphia based study conducted by Morrison et al (2017) showed that proximity to bars and restaurants was associated with decreased odds of (non-gun) assault before 1pm but with increased odds of assault after 7pm. Another Toronto based study (Cusimano et al 2010) used ambulance data to map incidents of violent injury across the city by time of day. The study found that during day time hours the greatest concentration of assaults were found in areas characterised by high proportions of social housing communities, homeless shelters, high unemployment rates and very low mean household incomes, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In Worcester (United Kingdom) patterns of alcohol-related crime and disorder in the city centre were associated with various characteristics of the functional environment, with higher rates along the key route ways towards residential areas and retail zones, and close to functional sites such as the railway station and the shopping centre (Bromley and Nelson 2002). Similar studies on hotspots of violent injuries identified environmental features such as a high number of bars, recreation facilities, transit nodes, high density housing, public restrooms and homeless shelters (Braga et al 1999;Cusimano et al 2010;Walker and Schuurman 2012).…”
mentioning
confidence: 88%
“…We selected functions where alcohol can be bought or functions that attract risk populations such as homeless people. Relevant characteristics of the functional, social and built environment were selected based on results of previous studies mentioned in the introduction (for example Bromley and Nelson 2002;Braga et al 1999;Cusimano et al 2010;Walker and Schuurman 2012).…”
Section: Environmental Profilesmentioning
confidence: 99%